Liner container seasonal shipping revenue management - Wang, Yadong; Meng, Qiang; Du, Yuquan (Transportation research. Part B: methodological, 2015)
•Multi-type containers considered to investigate the container selection and transportation subject to containership volume and weight capacity constraints.•A realist bunker consumption rate function adopted considering the containership sailing speed and displacement.•A profit maximization MINLP model formulated to address the seasonal revenue management measures for liner shipping company.•A tailored branch and bound algorithm developed to calculate global ε-optimal solution in finite steps. This paper proposes a liner container seasonal shipping revenue management problem for a container shipping company. For a given weekly multi-type shipment demand pattern in a particular season, the proposed problem aims to maximize the total seasonal shipping profit by determining the number of multi-type containers to be transported and assigned on each container route, the number of containerships deployed on each ship route, and the sailing speed of containerships on each shipping leg subject to both the volume and capacity constraints of each containership. By adopting the realistic bunker consumption rate of a containership as a function of its sailing speed and payload (displacement), we develop a mixed-integer nonlinear programing with a nonconvex objective function for the proposed liner container seasonal shipping revenue management problem. A tailored branch and bound (B&B) method is designed to obtain the global ε-optimal solution of the model. Numerical experiments are finally conducted to assess the efficiency of the solution algorithm and to show the applicability of the developed model.